Implementation of Quality by Design for the Development and Validation of Pioglitazone Hydrochloride by RP-UPLC with Application to Formulated Forms. (19th December 2012) - Xavier, Cijo M.; Basavaiah, Kanakapura
Abstract : Quality by Design (QbD) is a philosophy that refines the level of knowledge associated with a product that uses process understanding to deliver a product with the desired critical quality attributes. The objective of this study was to develop an integrated multivariate QbD approach to develop and quantify the constituent concentrations of pioglitazone hydrochloride (PGZ) drug in its pure and formulated forms. To facilitate studies investigating the determination of PGZ in bulk drug and its pharmaceutical formulations, a rapid UPLC method was developed and validated for the determination of PGZ accompanied by its degradation studies in different stress conditions. The method fulfilled validation criteria and was shown to be sensitive, with limits of detection (LOD) and quantitation (LOQ) of 0.01 and 0.05 μ g mL −1, respectively. The percent relative standard deviations for robustness and ruggedness were observed within the range of 0.1–1.74. The calibration graph was linear in the range of 0.05–300 μ g mL −1 . The applicability of the method was shown by analysis of formulated drug samples and spiked human urine. The proposed method can be used for routine analysis in quality controlled laboratories for its bulk and formulated product and this is the first reported UPLC method for the assay of PGZ.